Layout : 50 real-life projects uncovered. - Moore, Rodney J., ....- (Gloucester : Rockport, 2004)
In this newest installment in Rockport's popular Design Secrets series, readers are invited inside the creative process that goes into designing a winning layout. This book features 50 real-life layout design projects and looks behind the scenes, uncovering the design processes that produced the end results. Original plans, sketches, visuals, interim drawings and presentations, each accompanied by informative text and captions, show how designers present their ideas and solve problems. Each featured design project is shown in detail from concept to completion and all the stages in between. Rodney J. Moore focuses on the layout process for a wide variety of real-life graphic design projects, exploring the hows and whys of the layout's final look. He answers questions such as: Where did the idea come from? Why did the designer approach the problem this way? What failures did the designer encounter along the way? How did the designer achieve the end result? This book provides an over-the-shoulder perspective on the design process for 50 hardworking layouts.
Keywords: Grafische vormgeving